Kualitas Limbah Cair Industri Tahu Berdasarkan Parameter BOD, pH, COD dan TSS di Kelurahan Bara-Baraya Timur Kota Makassar - Novi Poni Harwani; Sartika Fathir Rahman; Siti Maifa Diapati (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2021)
Tofu industrial liquid waste contains high organic matter, if it is discharged into the environment without being processed first, it will have a negative impact in the form of environmental pollution. Currently, most of the tofu industry is still a small household scale industry, for example in Bara-baraya one of the tofu industries is not equipped with a wastewater treatment unit. The Bara-baraya tofu industry is located right in the middle of a residential area, so this can cause disturbance to the surrounding environment. This study aims to determine the quality of the tofu industrial wastewater in the Bara-Baraya Timur Village, Makassar City in terms of pH, BOD, COD, and TSS parameters. The type of research used is observational research with a descriptive approach. The method of examining samples from the parameters of BOD, COD, TSS and pH in the tofu industrial wastewater refers to the SNI for water quality testing methods and is examined at the Makassar Health Laboratory Center. The results of the inspection of the quality of tofu waste water compared to the Minister of Environment Regulation No. 5/2014 are the pH parameter 3.85 (not eligible), COD parameter 499 mg/L (not eligible), TSS parameter 4.777.50 mg/L (not eligible), and BOD parameters 1.771.88 mg/L (not eligible). The conclusion in this study is the quality of tofu wastewater in waste samples that have not undergone treatment at the wastewater treatment plant (IPAL) located in the tofu industry located in RW 4, Bara-Baraya Village, Makassar City, does not meet the requirements and exceeds the quality standards that have been set. determined by the government so that it can cause pollution to the surrounding environment.